Human fibroblast matrices bio-assembled under macromolecular crowding support stable propagation of human embryonic stem cells - Peng, Yanxian; Lyko, Frank (Journal of tissue engineering and regenerative medicine, 2012)
Stable pluripotent feeder-free propagation of human embryonic stem cells (hESCs) prior to their therapeutic applications remains a major challenge. Matrigel™ (BD Singapore) is a murine sarcoma-derived extracellular matrix (ECM) widely used as a cell-free support combined with conditioned or chemically defined media; however, inherent xenogenic and immunological threats invalidate it for clinical applications. Using human fibrogenic cells to generate ECM is promising but currently suffers from inefficient and time-consuming deposition in vitro. We recently showed that macromolecular crowding (MMC) accelerated ECM deposition substantially in vitro. In the current study, we used dextran sulfate 500 kDa as a macromolecular crowder to induce WI-38 fetal human lung fibroblasts at 0.5% serum condition to deposit human ECM in three days. After decellularization, the generated ECMs allowed stable propagation of H9 hESCs over 20 passages in chemically-defined medium (mTEsR1) with an overall improved outcome compared to Matrigel in terms of population doubling while retaining teratoma formation and differentiation capacity. Of significance, only ECMs generated by MMC allowed the successful propagation of hESCs. ECMs were highly complex and in contrast to Matrigel, contained no vitronectin but did contain collagen XII, ig-h3 and novel for hESC-supporting human matrices, substantial amounts of transglutaminase 2. Genome-wide analysis of promoter DNA methylation states revealed high overall similarity between human ECM- and Matrigel-cultured hESCs; however, distinct differences were observed with 49 genes associated with a variety of cellular functions. Thus, human ECMs deposited by MMC by selected fibroblast lines are a suitable human microenvironment for stable hESC propagation and clinically translational settings. Copyright © 2012 John Wiley & Sons, Ltd.
First published: 03 July 2012
Gesehen am 24.10.2018